Dork diaries : pop star Vol. 3 - Russell, Rachel Renée (London : Simon and Schuster, 2014)
More diary entries and doodles from Nikki's not-so-fabulous life... Let the spotlight showdown commence...Nikki Maxwell's school is holding a talent competition and Nikki can't wait to start practising dance moves with her BFFs, Chloe and Zoey, and impressing Brandon, her crush, with her singing skills! But then Nikki finds out that her arch-nemesis, MacKenzie, is entering the contest too, and she's determined to steal the limelight from Nikki and her friends. Can a dork like Nikki take on the most popular girl in school and win?
Keywords: Maxwell, Nikki (Fictitious character) -- Maxwell, Nikki (Fictitious character) -- Juvenile fiction -- Friendship -- Fiction -- Diary -- Juvenile fiction -- Talent shows -- Singers -- Juvenile fiction -- Talent shows -- Juvenile fiction -- Humorous stories